A study on the genus Stenus Latreille from Zhuji City of Zhejiang, East China (Coleoptera, Staphylinidae) - Tang, Liang; Liu, Sheng-Nan; Zhao, Tie-Xiong (Zootaxa, 2017)
The species of the genus Stenus Latreille from Zhuji city, Zhejiang, East China, are reviewed. Two species are described as new: Stenus dongbaishanus Tang, Liu & Zhao, sp. n., and S. zhejiangensis Tang, Liu & Zhao, sp. n. Stenus gastralis Fauvel, 1895 is newly recorded from China, and S. alumoenus Rougemont, 1981, S. dissimilis Sharp, 1874 and S. kuatunensis L. Benick, 1942 are newly recorded from Zhejiang. Diagnostic characters of the new species and newly recorded species are illustrated and a key to species of Zhuji city is provided.